POTENSI KEBERADAAN FITOKIMIA KAMALAKA (Phyllanthus emblica) BERDASARKAN PERBEDAAN KETINGGIAN TEMPAT TUMBUH - Dyah Novita Sari Tarakanita; Trisnu Satriadi; Ahmad Jauhari (Jurnal Sylva Scienteae, 2020)
The plant kamalaka (Phyllanthus emblica) belongs to plants that are fire resistant and are pioneer plants or grow first after forest fires.The plant has function as a medicinal plants. The purpose research was to analyzepresence phytochemical from kamalaka plants based on the differences in growing altitude. This research was carried in three different locations, namely in high altitude of growing location which in Mandiangin, medium altitude of growing location which in Pelaihari and low altitude of growing location which in Landasan Ulin. The method used was by observing and sampling in the field and also identifying the presence phytochemicalthrough lab tests with the Harborne method. The results showed the alkaloid test with Mayer reactor wasn’t detected or negative results, whereas in Wagner and Dragendorff reactors the presence alkaloids were varied which showed positive results ranging from weak positive (+), medium positive (++) and strong positive(+++). The flavonoid testalso were obtained variedpositive results,ranging from weak positive (+), medium positive (++) and strong positive (+++). The characteristicsof growing locations towards the presence alkaloids and flavonoids on each locations were different. This wascaused by such as light intensity, temperature and humidity, tree diameter, altitude locationsand also dominant soil types. In high altitude and in medium altitude of growing location were found that the presence alkaloid compounds were weak and the presence flavonoids were strong, while in low altitude of growing location the presencealkaloid compounds were strong and the presence flavonoid were weak.Keywords: Kamalaka; Alkaloids; Flavonoids and Altitude of Growing Location